IMPLEMENTASI PENDEKATAN KONTEKSTUAL DALAM PEMBELAJARAN MENULIS TEKS PERSUASI SISWA KELAS VIII B SMP NEGERI 11 KOTA JAMBI TAHUN AJARAN 2021/2022 - Dea Juliza, Agna; Karim, Maizar; D., Yusra (Penerbit Lafadz Jaya, 2024)
This research aims to describe the implementation of a contextual approach in learning to write persuasive texts in class VIII B of SMP Negeri 11 Jambi City. Learning Indonesian cannot be separated from the approach methods in delivering the material. One approach used is a contextual approach. The purpose of this research was to find out how to implement contextual application in Indonesian language learning of persuasive text material for class VIII B students at SMP Negeri 11 Jambi City. This type of research is descriptive qualitative, data collection in this research was carried out by observing teachers, students and classes, interviews and documentation. The subject of this research is the Indonesian language study teacher in class VIII B of SMP Negeri 11 Jambi City. The implementation of the contextual approach was carried out ideally and this has been proven by the researchers' interviews with teachers, students and monitoring carried out during the teaching and learning process and the supporting factors were the enthusiasm of the students in participating in the learning, as well as adequate facilities and infrastructure. Based on the research results, it can be concluded that the application of a contextual approach to learning to write persuasive texts for class VIII B students at SMP Negeri 11 Jambi City has been implemented quite well.